How does psychological well-being mediate the relationship between resilience and depression among Muslim students? - Diponegoro, Ahmad Muhammad; Widiana, Herlina Siwi (Humanitas: Indonesian Psychological Journal, 2025)
Depression is a mental health concern that is prevalent worldwide, including among university students. This study aims to examine the mediating role of psychological well-being on the relationship between resilience and depression among Muslim students in Indonesia. Two hundred forty Muslim students at one Islamic college institution participated in this study. Participants completed the Indonesian version of the Center for Epidemiological Studies Depression Scale, Psychological Well-being Scale, and Connor-Davidson Resilience Scale. The results show resilience has a significant negative correlation with depression; the higher the resilience, the lower the depression will be. Moreover, the mediation analysis shows that psychological well-being fully mediated the relationship between resilience and depression among Muslim students. The relationship between psychological well-being and depression in Muslim students who were participants in this research can be explained using the dual continua mental health paradigm. Participants tend to have either a high level of psychological well-being and depression or low levels of psychological well-being and depression.